Intradural Intramedullary Mixed Type Hemangioma: Optimizing the Surgical Management through Intraoperative Neurophysiological Monitoring - Ahmad Jabir Rahyussalim; Adrian Situmeang; Ahmad Yanuar Safri; Zulfa Indah K. Fadhly (Case Reports in Surgery)
Intradural intramedullary mixed type hemangioma is a rare histotype of primary spinal cord tumors, though it can carry a severe clinical burden leading to limb dysfunction or motor and sensory disturbances. Timely intervention with radical resection is the hallmark of treatment but achieving it is not an easy task even for experienced neurosurgeons. We herein present an exemplificative case presenting with sudden paraplegia in which total resection was achieved under intraoperative neurophysiology monitoring. A thorough discussion on the operative technique and the role of neuromonitoring in allowing a safe surgical management of primary spinal cord tumors is presented.